2011
DOI: 10.1091/mbc.e10-11-0873
|View full text |Cite
|
Sign up to set email alerts
|

C4orf41 and TTC-15 are mammalian TRAPP components with a role at an early stage in ER-to-Golgi trafficking

Abstract: Using two different TRAPP subunits as bait, we have identified four additional components of this human vesicle–tethering complex. Functional studies suggest that TRAPP functions early in ER-to-Golgi traffic, at or before the level of the ERGIC compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(194 citation statements)
references
References 43 publications
17
175
2
Order By: Relevance
“…It was recently reported that depletion of the mammalian homolog of Trs85 (mTrs85) leads to a reduction in autophagosome formation (16), however, to date, only one TRAPP complex has been described in mammals (17,18). Since the roles of Ypt1 and its homolog Rab1 appear to be highly conserved from yeast to man (12), we asked if mTrs85 is a component of a TRAPP complex that is analogous to yeast TRAPPIII.…”
Section: Trs85 Is a Component Of A Transport Protein Particle III Commentioning
confidence: 99%
“…It was recently reported that depletion of the mammalian homolog of Trs85 (mTrs85) leads to a reduction in autophagosome formation (16), however, to date, only one TRAPP complex has been described in mammals (17,18). Since the roles of Ypt1 and its homolog Rab1 appear to be highly conserved from yeast to man (12), we asked if mTrs85 is a component of a TRAPP complex that is analogous to yeast TRAPPIII.…”
Section: Trs85 Is a Component Of A Transport Protein Particle III Commentioning
confidence: 99%
“…Unlike yeasts, no small-core TRAPP complex equivalent to the yeast TRAPP I complex appears to be present in mammals, suggesting that TRAPP complexes play differently roles in early secretory trafficking in yeasts and mammals (Scrivens et al, 2011). On the other hand, mammals contain two functionally different TRAPP complexes, named mTRAPP II and mTRAPP III, that are broadly similar to but clearly different in terms of their subunit composition from the yeast TRAPP II complex and TRAPP III complex, respectively.…”
Section: Trapp Complexesmentioning
confidence: 99%
“…2 and Sacher et al, 2008). Fibroblasts from patients with TRAPPC11 or TRAPPC2 mutations (Bögershausen et al, 2013;Scrivens et al, 2009), and cultured cells depleted of TRAPPC11 (Scrivens et al, 2011;Wendler et al, 2010) display Golgi fragmentation and secretory protein retention. However, when these proteins are depleted in whole organisms their cell-specific roles are uncovered: patients with TRAPPC2 mutation develop spondyloepiphyseal dysplasia tarda (SEDT) distinguished by skeletal defects, short stature and microcephaly (Gedeon et al, 1999;Huson et al, 1993).…”
Section: Diseases Caused By Secretory Pathway Disruption In Zebrafishmentioning
confidence: 99%